A latent class analysis of psychiatric symptom profiles associated with past-month methamphetamine use. (April 2021) - Voce, Alexandra; Burns, Richard; Castle, David; Calabria, Bianca; McKetin, Rebecca
Highlights: We identified two distinct psychotic syndromes associated with methamphetamine use. An extensive psychiatric symptom profile linked to diagnosis of schizophrenia (SZ). A profile of paranoia and hallucinations linked to methamphetamine psychosis (MAP). These data-driven syndromes align with diagnostic constructs of MAP and SZ. A discrete category for MAP is necessary to capture this heterogeneity in psychosis. Abstract: We explored latent psychiatric symptom profiles associated with methamphetamine use, and examined how these corresponded to diagnoses of schizophrenia (SZ) and methamphetamine-associated psychosis (MAP). We assessed psychiatric symptoms among 160 people who had used methamphetamine in the past month. Psychiatric symptoms were defined as a score of 4+ on Brief Psychiatric Rating Scale (BPRS) items. Diagnoses were made using the Composite International Diagnostic Interview (CIDI). Participants were defined as having MAP if they met symptom criteria for SZ, but symptoms were considered to be always the result of substance use. Latent class analysis identified three classes. Class one (44% of participants) had a low probability of most BPRS symptoms; 4% met criteria for SZ, 51% for MAP. Class two (31% of participants) had a higher probability hallucinations and suspiciousness (37–46%); 72% met criteria for MAP, and 7% for SZ. Class three (25% of participants) had the highest probability for all positive psychotic symptoms (hallucinations, suspiciousness, grandiosity, unusual thought content; 32–82%), and reported activation, conceptual disorganisation, and tension (35% met criteria for SZ and 17% for MAP). We found three distinct classes of psychiatric symptom profiles, two of which showed partial alignment with diagnostic constructs of SZ and MAP.